Dodecyl sulfate-induced fast faradic process in nickel cobalt oxide–reduced graphite oxide composite material and its application for asymmetric supercapacitor device - Wang, Xu (2013)
In this contribution, we report a facile preparation method of nickel cobalt oxide–reduced graphite oxide (NiCo2O4–rGO) composite material. A fast Faradic process has been realized by sodium dodecyl sulfate (SDS)-induced ultrasmall NiCo2O4 nanocrystals on rGO. As a result, this composite material gives a high specific capacitance of 1222 F g−1 at 0.5 A g−1 and 768 F g−1 at 40 A g−1, showing an outstanding rate capability. An asymmetric supercapacitor device with high energy and power densities has been successfully assembled based on NiCo2O4–rGO composite material and activated carbon. The optimized device shows a high energy density of 23.32 Wh kg−1 at a power density of 324.9 W kg−1. In addition, this asymmetric device shows good stability towards multistage current charge–discharge cycles.